Faktor yang berkaitan dengan pencapaian Matematik pelajar Melayu Sekolah Menengah Agama daerah Pontian - Mazalan, Mohd. Faizal (2012)
Mathematics is one of the most important courses taught either in primary or secondary schools. At this juncture, it is observed that the level of mastery has not reached tits expected level. Therefore, factors pertinent to the achievement of Mathematics have drawn the interest into this study. This study aims at identifying the leading factors to the achievement of Mathematics amongst Malay students in the religious school in the district of Pontian. A number of 158 Form 4 students from 2 different schools in the district of Pontian have been taken in as the respondents of this study. A set of questionnaires containing 30 items employing the Likert scale of measurement and Alpha a=0.82 reliability coefficient are used as a substantive instrument in the course of this research. Data are collected and subsequently analysed using the Statistical Package for the Social Science (SPSS) Version 17.0. Descriptive statistics and inferences are used to elicit the outcome on important information pertaining to the sex factor, Mathematics achievement in UPSR, Mathematics achievement in PMR, size of the family, education background of the parents, family income, interest, perceptions, parental encouragements, as well as roles and encouragements from the teachers and peers. The outcome of the study reveals that the significant nexus to the Mathematics achievement in PMR is closely derived from the Mathematics achievement in UPSR, students’ interest, education background of their parents, and peer influence. On the other hand, factors that bear no significance in the achievement of Mathematics in PMR are the students’ perception towards the subject itself, size of the family, family income, as well as the encouragements of their parents and teachers.